A Numerical Study of Eastern Oyster (Crassostrea virginica) Larval Growth and Dispersal in Barataria Estuary, Louisiana, USA - Zhengchen Zang; Z. George Xue; Shaye E. Sable; Megan K. La Peyre; Kenneth A. Rose; Timothy A. Stephens; Brady Carter; David C. Lindquist; Yanda Ou; Ziyan Lei (Estuaries and Coasts, 2026)

Perinatal exposure to delta-9-tetrahydrocannabinol (THC) alters goal-directed behavior and dopamine functioning in wistar rats - Monica S. Carbajal; Rebecca C. Crenshaw; Victoria E. Williams; Laura G. Billings; Chelsea M. Dixon; Deranda B. Lester; Helen J. K. Sable (Psychopharmacology, 2026)
Rationale Cannabis use during 2021pregnancy is common as many pregnant women consider cannabis as a safe way to alleviate symptoms associated with pregnancy because it is “natural”. However, clinical evidence links perinatal cannabis exposure to externalizing behavior in offspring. In preclinical research, most studies focus on exposure to the psychoactive constituent of cannabis, delta-9-tetrahydrocannabinol (THC). THC is lipophilic, allowing it to cross the placental barrier and be secreted in maternal milk, thereby exposing the fetus/neonate. Objective We used operant procedures to measure motivation and impulsivity in adult offspring perinatally exposed to THC. Methods Dams were orally exposed to 0 or 5 mg/kg/day THC daily from 14 days prior to breeding to postnatal day (PND) 14. Differential reinforcement of high rates (DRH) and differential reinforcement of low rates (DRL) of responding tasks were used to examine motivation and impulsive action. We also measured dopamine (DA) functioning in the medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) via in vivo fixed potential amperometry in littermates of rats that completed behavioral testing. Results Perinatal THC exposure had minimal effects on impulsive action measures during DRL 15s. Rather, perinatal THC exposure decreased DRL 15s burst responses and completed trials in both sexes, and reinforcers earned in THC-exposed males. Decreased lever presses during DRH were observed in both sexes perinatally exposed to THC, as well as fewer reinforcers in THC-exposed males. THC exposure did not alter baseline DA release in the NAc or mPFC, but did attenuate the dopaminergic response to cocaine in the NAc. Conclusions These results suggest perinatal exposure to THC can decrease motivation to work for reinforcers during high-effort tasks, that this effect may be more pronounced in males, and that the “amotivational state” resulting from perinatal THC exposure may be due to reinforcer devaluation. Keywords : oral THC, developmental neurotoxicology, amotivational syndrome, mesocorticolimbic dopamine.

Using Multiple Ecological Models to Inform Environmental Decision-Making - Kristy A. Lewis; Kenneth A. Rose; Kim de Mutsert; Shaye Sable; Cameron Ainsworth; Damian C. Brady; Howard Townsend (Frontiers in Marine Science, 2021)
Coastal ecosystems are experiencing degradation from compound impacts of climate change and multiple anthropogenic disturbances. These pressures often act synergistically and complicate designing effective conservation measures; consequently, large-scale coastal restoration actions become a wicked problem. The purpose of this study was to use two different food web models in a coordinated manner to inform resource managers in their assessment of the ecological effects of a large-scale marsh restoration project. A team was formed that included the model developers and outside scientists, who were asked to use available model results of the calibrated simulations of an Ecopath with Ecosim (EwE) model and a Comprehensive Aquatic Systems Model (CASM), both designed to describe the structure and energetics of the Barataria Bay, Louisiana, United States food web. Both models offer somewhat different depictions of the predator-prey and competitive interactions of species within the food web, and how environmental conditions affect the species biomass pools and energetics. Collectively, the team evaluated the strengths of each model and derived a common set of indicator variables from model outputs that provided information on the structure and energy flow of the simulated food web. Considering the different modeling structures and calibration approaches, indicators were interpreted within and between models. Use of both models enabled a robust determination that: (1) Detritus plays a vital role in the energetics of the system; (2) The food web responds to spring high flow seasons by increasing productivity through specific, dominant pathways; (3) The trophic pyramid is truncated; (4) Compared to other estuaries, this system has redundant pathways for energy transfer. These findings indicate that the food web appears to be resilient to disturbance because of a detritus energy reserve, most consumer biomass consists of low trophic level, high turnover species, and redundant energy pathways exist. This information provides context to decision-makers for assessing possible basin-scale impacts on fish and shellfish resources of a proposed large-scale restoration project. The use of multiple models in a coordinated but not overly constrained way, as demonstrated here, provides a significant step toward co-production of knowledge for use in resource management decisions.

Application of Species Distribution Models to Identify Estuarine Hot Spots for Juvenile Nekton - Ann Commagere Hijuelos; Shaye E. Sable; Ann M. O’Connell; James P. Geaghan; David C. Lindquist; Eric D. White (Estuaries and Coasts, 2017)

Efficacy of caspofungin as salvage therapy for invasive aspergillosis compared to standard therapy in a historical cohort - J. W. Hiemenz; I. I. Raad; J. A. Maertens; R. Y. Hachem; A. J. Saah; C. A. Sable; J. A. Chodakewitz; M. E. Severino; P. Saddier; R. S. Berman; D. M. Ryan; M. J. DiNubile; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Efficacy and safety of caspofungin therapy in elderly patients with proven or suspected invasive fungal infections - M. J. DiNubile; K. M. Strohmaier; R. J. Lupinacci; A. R. Meibohm; C. A. Sable; N. A. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Contrasting grain size and componentry in complex proximal deposits of the 1886 Tarawera basaltic Plinian eruption - R. J. Carey; B. F. Houghton; J. E. Sable; C. J. N. Wilson (Bulletin of Volcanology, 2007)

Multicenter retrospective development and validation of a clinical prediction rule for nosocomial invasive candidiasis in the intensive care setting - L. Ostrosky-Zeichner; C. Sable; J. Sobel; B. D. Alexander; G. Donowitz; V. Kan; C. A. Kauffman; D. Kett; R. A. Larsen; V. Morrison; M. Nucci; P. G. Pappas; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Complex proximal sedimentation from Plinian plumes: the example of Tarawera 1886 - J. E. Sable; B. F. Houghton; C. J. N. Wilson; R. J. Carey (Bulletin of Volcanology, 2006)

Global Distribution and Outcomes for Candida Species Causing Invasive Candidiasis: Results from an International Randomized Double-Blind Study of Caspofungin Versus Amphotericin B for the Treatment of Invasive Candidiasis - A. L. Colombo; J. Perfect; M. DiNubile; K. Bartizal; M. Motyl; P. Hicks; R. Lupinacci; C. Sable; N. Kartsonis (European Journal of Clinical Microbiology & Infectious Diseases, 2003)